Pro-development Investments of Municipalities and the Concept of Socially Responsible Investment - Małkowska, Agnieszka; Uhruska, Małgorzata; Żak, Agnieszka (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article discusses the engagement of local governments in socially responsible investment. Due to the goals and tasks taken by municipalities in the area of investment policy, which is a crucial part of general local development policy, there is a need to ask: In what sense do municipal authorities contribute to socially responsible investments and support the sustainable development of local areas? This issue is considered in relation to the municipality’s own investment and to investment undertaken by other entities in municipalities. In their conclusions, the authors emphasize the key circumstances that reflect municipalities’ contribution to public and private socially responsible investments, mainly in the following areas: analysing and locating investment needs on a hierarchy, defining strategic documents, establishing selection criteria and standards for implementing and evaluating investments. Finally, the article presents the main causes and consequences of municipal investment activities, which stand in contrast to the idea of responsible investment.